Do Infants Learn from Isolated Words? An Ecological Study. Issue 1 (2nd January 2019) - Keren-Portnoy, Tamar; Vihman, Marilyn; Fisher, Robin Lindop
ABSTRACT: Researchers disagree as to the importance for infant language learning of isolated words, which occur relatively rarely in input speech. Brent and Siskind (2001) showed that the first words infants produce are words their mothers used most frequently in isolation. Here we investigate the long-term effects of presentation mode on recognition memory for word forms. In two experiments we assess whether 12-month-old infants remember novel words presented in the home, over a three-week period: (i) in isolation or (ii) sentence-finally. When tested with word lists infants recognize words that had been presented in isolation, but not those that had been presented sentence-finally. They fail to recognise the trained words when tested with a segmentation task, regardless of presentation mode during the training. Our results indicate that the relatively small proportion of words produced in isolation in the input likely play a disproportionate role in the early period of language learning.